Self-Care Behavior and Associated Factors in the Elderly with Hypertension - Raden Roro Dewi Rahmawaty Aktyani Putri; Wimar Anugrah Romadhon; Tri Ratna Kolopaking (Journal of Ners and Midwifery, 2022)
Hypertension is one of the main risk factors for life-threatening cardiovascular disease and is often called the silent killerÂ The results of basic health research in 2018 suffered from hypertension were the most in the elderly aged 55 to 64 years (55.2%). Hypertension in the elderly is a chronic disease that requires disease care management including regular blood pressure control and self-care behavior programs to prevent further complications. This study aims to determine the factors related to self-care behavior in hypertensive elderly in the Integrated Health Care Center of elderly, Srikandi, Turi Sub District, Community Health Centers of Sukorejo, Sukorejo district, Blitar. The method used in this study was an analytical descriptive study with a cross-sectional approach conducted on 38 hypertensive elderly people. The study was conducted from January to February 2022. Analysis data using multiple linear regression analysis to ascertain the possible factors that influence self-care behavior. Based on this study, the Rank Spearman correlation test results, the factor that correlated with self-care behavior was level of education and time living with diagnosed hypertension with a Sig (2-tailed) value of 0.008; 0,000 with a correlation coefficient is positive, the value of 0.427; 0.605. so that theÂ relationship between the two variables is unidirectional. This study recommends that community nurses must understand the factors that influence self-care behavior in hypertensive clients in the community so that they are able to provide appropriate nursing care.